Reação de figueiras a três espécies de nematoides-das-galhas - Costa, Marylia Gabriella Silva [UNESP]; Correia, Érika Cristina Souza da Silva [UNESP]; dos Reis, Luis Lessi; Wilcken, Silvia Renata Siciliano [UNESP] (FapUNIFESP (SciELO), 2015)
Root-knot nematodes are the main soil pathogens of fig culture around the world. The aim of this study was to evaluate the reaction of fig genotypes to M. javanica, M. incognita and M. enterolobii, for using as rootstocks. Plants were inoculated with 5,000 eggs of the nematode test. Gall index, egg mass index and reproduction factor were evaluated at 120 days after inoculation. All genotypes were susceptible to M. javanica, M. incognita and M. enterolobii.
Reaction of fig tree to three species of root-knot nematodes
Keywords: Ficus carica L; Meloidogyne; Resistance